THE RELEVANCE OF PROPRIETY AND SELF-COMMAND IN ADAM SMITH'S THEORY OF MORAL SENTIMENTS. Issue 1 (2020) - Montes, Leonidas
Abstract: Propriety and self-command are distinctive and complex Smithian concepts. This essay attempts to shed more light on the meaning and significance of propriety and the virtue of self-command. After a brief introduction on the recent reappraisal of The Theory of Moral Sentiments (TMS), a short analysis of Smith's crucial idea of sympathy follows. Then the relevance of propriety is discussed and some connections between propriety and the virtue of self-command are explored. Finally, the importance of Smith's self-command is reassessed, paying attention to its origins and philosophical implications. It is noteworthy that, through self-command and propriety, TMS stresses the role of intentions and motivations. By doing so, Adam Smith opens up new threads to rethink personal liberty and its ethical importance for political economy.